2011
DOI: 10.1063/1.3640416
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical structure and spin order of Gd13 cluster

Abstract: The spin-polarized generalized gradient approximation to the density-functional theory has been used to determine the lowest energy structure, electronic structure, and magnetic property of Gd(13) cluster. Our results show that the ionic bonding is combined with the covalent characteristics in stabilizing the Gd cluster. The ferrimagnetic icosahedron is found to be the lowest energy configuration, in which the centered Gd atom couples antiferromagnetically with the rest Gd atoms surrounding it. No spin non-col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 58 publications
3
12
1
Order By: Relevance
“…In this paper, we present such a study by focusing on the * pjena@vcu.edu Gd 13 cluster, which is a prototypical strongly correlated cluster with highly localized f electrons. This choice was dictated not only because of the anomalous magnetic moment/atom of Gd 13 which is smaller than its bulk value, but also to address a long-standing controversy in both experimental [13,14] and theoretical [15,16] results of its equilibrium geometry, magnetic moment, and temperature dependence. Using density functional theory with self-consistently determined U [17], which is smaller than its bulk value; we show that both U and spin canting are needed to explain the anomalous magnetic moment and coupling in the Gd 13 cluster.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we present such a study by focusing on the * pjena@vcu.edu Gd 13 cluster, which is a prototypical strongly correlated cluster with highly localized f electrons. This choice was dictated not only because of the anomalous magnetic moment/atom of Gd 13 which is smaller than its bulk value, but also to address a long-standing controversy in both experimental [13,14] and theoretical [15,16] results of its equilibrium geometry, magnetic moment, and temperature dependence. Using density functional theory with self-consistently determined U [17], which is smaller than its bulk value; we show that both U and spin canting are needed to explain the anomalous magnetic moment and coupling in the Gd 13 cluster.…”
Section: Introductionmentioning
confidence: 99%
“…The valence electronic configurations consisting of (5s 2 5p 6 4f 7 5d 1 6s 2 ) and (4f 14 5d 10 6s 1 ) were considered for Gd and Au, respectively. The value of the effective on-site coulomb parameter was set to 7 eV for Gd which was found to be reasonable to describe the hcp-Gd crystal [16] and the Gd 2 dimer [17,18]. For example, the calculated magnetic moment of the bulk Gd is 7.6 μ B /atom, which is in good agreement with the experimental value of 7.63 μ B /atom [16].…”
Section: Methodsmentioning
confidence: 60%
“…In addition, the bonding preference of different atoms gives another efficient way to construct good candidates for the global minima or to reduce the configuration space. In our previous works, this method has been used to treat transition metal (TM) clusters [45][46][47][48][49][50][51] and lanthanide clusters, 18,20,28 for which the lowest energy structures we obtained were positively confirmed by the subsequent works using the unbiased global optimizations. 13,[52][53][54][55][56][57] Following above approaches, we consider all possible configurations for small sizes (n = 2-7), but construct a large number of initial configurations for large sizes (n = [8][9][10][11][12][13][14] primarily at the additive and substitutive patterns from the low-lying structures of Tb n±1 , e.g., three different binding modes are intensively examined for the adsorption of oxygen atom: atop, bridge, and hollow sites.…”
Section: Computational Proceduresmentioning
confidence: 69%
“…Recently, we have shown that in Gd 13 and (GdO) n clusters, the magnetic interaction between Gd atoms is medicated by the spin polarizations of Gd-s and d conduction electrons, and we determined that the Ruderman-Kittel-Kasuya-Yosida (RKKY) mechanism that governs the magnetic properties of lanthanide-based bulk materials is still valid in lanthanide clusters. 18,28 In these works, by comprehensively analyzing the dependence of exchange coupling parameter J(r i j ) on lanthanide atomic distance r i j , we found that J(r) oscillates between positive and negative in lanthanide cluster (favoring ferromagnetic and antiferromagnetic states), and it is sensitively dependent on atomic distance r around the equivalent structure. Therefore, a slight variation of Tb-Tb bondlengths induced by O atom would alternate the magnetic moment arrangements of Tb atoms, and thus prominently changes the total magnetic moments from Tb n cluster to Tb n O cluster.…”
Section: Effects Of Magnetic Propertiesmentioning
confidence: 96%
See 1 more Smart Citation